Fever, convulsions, and rash: a case report of neonatal lupus erythematosus with macrophage activation syndrome - Yu, Jing; Xue, Guohui; Liu, Xiaohui; Zhan, Chunlei; Huang, Jinshi (Frontiers in Pediatrics, 2024)
Neonatal lupus erythematosus (NLE) is a rare acquired autoimmune disease associated with the entry of maternal antibodies into the fetal circulation via the placenta during pregnancy. Macrophage activation syndrome (MAS) is a severe hyperinflammatory disease. Herein, we present a case of NLE with MAS accompanied by fever, convulsions, and rash. High-dose gamma globulin and non-shock doses of steroids can be used as a first-line treatment for NLE with MAS. Fever can be a clinical manifestation of NLE, especially cutaneous lupus. Rash recession could be used to judge whether the disease is effectively controlled by treatment.